TINJAUAN KONSEP GREEN DESIGN PADA RADIO MAGNO KARYA SINGGIH KARTONO - Ariani Ariani (Jurnal Dimensi Seni Rupa dan Desain, 2012)
Abstractthe idea of Green Design, normally viewed as an environmental-base design, currently become very crucial, especially at this time when we are becoming more conscious about negative impacts of aour recless actions for the nature. Hence , nowadays all designers ate challenged to not only dealing with the aesthtetics and usefulness aspects of an object, but also with the effort to minimize the damaging impacts to our surroundings. Magno Radio is one of Singgih Kartono work -of-art that the distinctive feature of that products is using sonokeling wood, mahogany, sengon, and pines for most of the material parts. Reffering to eco -design concept introduced by Victor Papanek, choices of raw materials, packages of the products and delivery of the products are three points that need to be carefully taken into account in the case of Singgih Kartnono's Magno Radio. It is clearly understood that cutting woods excessively will have potential destructive forces to our nature. Therefore, to avoid this, we need to use material wisely. In implementing Green Design we need to understand that the ultimate goal of that concept is to save our environment and our own lives Abstrak Wacana geren design atau sering diartikan sebagai design yang berwawasan lingkungan atau design yang ramah lingkungan, menjadi sanagat penting belakangan ini terlebih di saat kita semakin menaydari dampak kerusakan lingkungan yang terjadi sebagai akibat perilaku manusia terhadap alam yang kirang bijaksana. Dalam hal ini para desainer kini menghadapi tantangan , bukan hanya memaksimalkan dampak buruk bagi lingkungan tanpa menghabiskan lebih banyak sumber energi. Radio Magno adalah sebuah produk karya Singgih Kartono dengan ciri khas penggunaan material yang terbuat dari kayu sonokeling, mahoni, sengon dan pinus. Ditinjau dari konsep eco design yang dikemukakan oleh Victor Papanek, ada beberapa hal yang perlu diperhatikan pada radio Magno tersebut, yaitu pemilihan material/bahan baku, pengemasan/packaging produk, dan pengangkutan/pengiriman produk. Penggunaan kayu yang berlebihan memang berpotensi merusak alam, oleh karena itu diperlukan sikap yang bijak dalam penggunaannya. Kesadaran akan arti pentingnya penerapan wacana green design adalah salah satu usaha untuk menyelamatkan lingkungan dan kehidupan makhluk di bumi